2023
DOI: 10.1158/1535-7163.mct-22-0193
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Analysis of Savolitinib plus Osimertinib in an EGFR Mutation–Positive, MET-Amplified Non–Small Cell Lung Cancer Model

Abstract: Osimertinib is a third-generation, irreversible, oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), recommended as first-line treatment for patients with locally advanced/metastatic EGFR-mutation positive (EGFRm) non-small cell lung cancer (NSCLC). However, MET-amplification/overexpression is a common acquired osimertinib resistance mechanism. Savolitinib is an oral, potent, and highly selective MET-TKI; preliminary data suggest that combining osimertinib with savolitinib may overcom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…On the basis of a defined exposure–response relationship, it is suggested that PopPK models be developed to support dose individualization. Up to now, studies on PopPK have been conducted for a variety of antineoplastic drugs, including atezolizumab, 53 brentuximab vedotin, 54 busulfan, 9 , 11 , 55 dasatinib, 56 methotrexate, 7 , 57 , 58 sunitinib, 59 and vincristine 60 , 61 in pediatric patients and acalabrutinib, 62 afatinib, 63 atezolizumab, 53 brentuximab vedotin, 54 dostarlimab, 64 erlotinib, 65 necitumumab, 66 nivolumab, 67 pembrolizumab, 68 savolitinib plus osimertinib, 69 siltuximab, 70 and trastuzumab 71 in adults. Based on heterogeneous data, the quantification, and identification of variability and simulations, PopPK is an essential tool to individualize drug doses to reduce toxicity and improve patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of a defined exposure–response relationship, it is suggested that PopPK models be developed to support dose individualization. Up to now, studies on PopPK have been conducted for a variety of antineoplastic drugs, including atezolizumab, 53 brentuximab vedotin, 54 busulfan, 9 , 11 , 55 dasatinib, 56 methotrexate, 7 , 57 , 58 sunitinib, 59 and vincristine 60 , 61 in pediatric patients and acalabrutinib, 62 afatinib, 63 atezolizumab, 53 brentuximab vedotin, 54 dostarlimab, 64 erlotinib, 65 necitumumab, 66 nivolumab, 67 pembrolizumab, 68 savolitinib plus osimertinib, 69 siltuximab, 70 and trastuzumab 71 in adults. Based on heterogeneous data, the quantification, and identification of variability and simulations, PopPK is an essential tool to individualize drug doses to reduce toxicity and improve patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%